The Management of Indonesian Language Learning Based on Joyful Learning for Eighth-Grade Students at SMP Negeri 1 Kalikotes in the 2025/2026 Academic Year - Ginanjar Muktiharja; Sukini Sukini; Agus Yuliantoro (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
This study aimed to describe the management of Indonesian language learning based on Joyful Learning among eighth-grade students at SMP Negeri 1 Kalikotes in the 2025/2026 academic year. This study employed a qualitative approach with a single case study design. Data were collected through participatory observation, in-depth interviews, documentation studies, and open-ended questionnaires. The findings showed that the implementation of Joyful Learning had been conducted systematically through planning, implementation, and evaluation processes integrated with the principles of the Merdeka Curriculum. Teachers applied varied learning methods, interactive activities, and learning media to create an active, communicative, and enjoyable learning atmosphere. Learning evaluation was carried out continuously by emphasizing students’ participation and learning processes. The implementation of Joyful Learning was supported by teacher competence, school support, and adequate facilities, although several obstacles such as differences in students’ characteristics, literacy abilities, and limited learning time were still encountered. Overall, Joyful Learning contributed positively to improving student engagement and the quality of Indonesian language learning.